Os negócios jurídicos processuais no Novo Código de Processo Civil Brasileiro - Bocalon, João Paulo (2016)
This paper is aimed at assessing procedural agreements, such as the procedural flexibility technique, which is highly valued by Brazil's New Code of Civil Procedure. At the outset, this topic is researched from the standpoint of general procedural theory, in order to classify it within the context of its fundamental institutes. Later, this topic is looked at from the standpoint of general contract theory, confronting the problem regarding its defects and nullities. With these definitions, basic notions are established of the institute, such as concept, terminology, legal nature, guiding principles and a suggested classification. With the support of these technical cornerstones, the central problem is found, which is the pragmatic analysis of typical and atypical procedural contracts in Brazil's New Code of Civil Procedure. Keywords: Procedural agreements, Procedural flexibility, Procedural timetable, New Civil Code of Procedure